Delivering evidence-based upper limb rehabilitation for children with cerebral palsy: Barriers and enablers identified by three pediatric teams - Sakzewski, L.; Ziviani, J.; Boyd, Roslyn (2014)
This study aimed to identify barriers and enablers experienced by occupational therapists to delivering evidence-based upper limb intervention for children with unilateral cerebral palsy. Semistructured interviews informed by the Theoretical Domains Framework were conducted with nine occupational therapists from three teams to ascertain barriers and enablers to implementing five evidence criteria. A key barrier was lack of knowledge of current evidence for upper limb therapies for children with unilateral cerebral palsy. Therapists were confident in delivering goal-directed bimanual occupational therapy, but less knowledgeable and skilled, and hence confident in providing constraint therapy. Strategies to increase dose of therapy were identified as greater use of home programs and group-based interventions; however, therapists indicated the need for further education and skill development in these areas. In order to increase the uptake of research evidence into practice, findings from this study will be used to inform context-specific, individually targeted implementation strategies.